Peran E-Hrm (Electronic Human Resource Management) Dalam Meningkatkan Kinerja Organisasi Di Era Digital - Herman Putra Zamasi (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Digital transformation has transformed human resource management from an administrative function to a strategic one. This study aims to analyze how the implementation of Electronic Human Resource Management (E-HRM) contributes to improved organizational performance. Using a literature review method, this study explores three levels of E-HRM: operational, relational, and strategic. The study results indicate that E-HRM improves time efficiency, data accuracy, and employee satisfaction, which collectively drive organizational productivity. However, its success depends heavily on the readiness of technological infrastructure and an adaptive organizational culture.